Empowering critical thinking and self-awareness through biology learning mosquito larva control project - Yena Harmelayati; Novantrya Salidar; Ari Widodo; Sariwulan Diana (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study investigates the effectiveness of a mosquito larva control project in enhancing students’ critical thinking skills and self-awareness within biology learning. Contemporary biology education increasingly demands the integration of cognitive and affective competencies through authentic learning contexts. A mixed-methods experimental design was employed involving 27 high school students in Bandung. Quantitative data were collected through pretest–posttest measures of critical thinking and a self-awareness questionnaire, while qualitative data were derived from student experiments, reflections, and group-based project activities. The intervention was implemented through a Problem-Based Learning (PBL) framework, encompassing problem identification, field investigation, and the design and testing of mosquito larva control solutions. Quantitative analysis using N-Gain indicated a moderate improvement in critical thinking skills (N-Gain = 0.7) and a high level of self-awareness (mean = 4.29). Qualitative findings revealed that students actively engaged in data-driven discussions, demonstrated analytical reasoning, and developed reflective awareness of their role in environmental health contexts. Most student groups successfully designed and implemented functional larval control strategies based on empirical observations.These findings suggest that the mosquito larva control project is effective in simultaneously strengthening students’ higher-order thinking skills and ecological self-awareness. The effectiveness of this approach may be further enhanced through extended project duration, structured reflective activities, and targeted teacher facilitation focusing on analytical and evaluative processes.